Development of Test Vessel for Gas Insulation Breakdown Test - Ayuamira Zahari; Hidayat Zainuddin; Muhammad Saufi Kamarudin; Nur Farhani Ambo; Jamaludin Mohd Wari; Imran Sutan Chairul (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper discusses a new test vessel developed to investigate the breakdown test performance of gas insulation. The test vessel is equipped with certain specialty including pressure chamber and control measures. Through help from a steering, it is provide of controlling the gap length of the electrodes without the need of removing the gas. Other control measures include humidity, temperature, and pressure readings. The humidity and temperature are read wirelessly and from the readings, the necessary atmospheric corrections can be made according to standards. The developed vessel is then tested with AC breakdown test using air with various gap lengths and various electrode configurations. There are two types of electrode configuration used in this project i.e., rod (R0.5)-plane and plane-plane.